Improving the Mathematics Ability using Quantum Learning Method for Elementary Students - Santoso, Adi; Wibowo, Setiawan Edi; Raharja, Setya; Bafirman, Bafirman (STKIP Singkawang, 2024)
The implementation of an appropriate learning model can enhance students' knowledge of fundamental mathematical concepts. The objective of this research is to enhance the ability of elementary school students to calculate the area of a rectangle by employing the quantum learning method. This research was conducted in a classroom setting and consists of seven steps: identifying issues, selecting strategies, compiling learning scenarios, exercising learning scenarios, determining success criteria, implementing scenarios, observing, and reflecting. Observation, interviews, written tests, and documentation were employed to gather the research data. This was followed by quantitative and qualitative analyses of the data. The study’s findings suggest that the quantum learning model has the potential to enhance student learning assessment results by facilitating the determination of the area of a rectangle. Additionally, it has been demonstrated to increase student engagement and interest in the learning process. Conversely, educators develop a greater capacity for creativity and proficiency in the teaching of mathematics